Studi Fenomenologi tentang Dukungan Pemerintah Desa dalam Penanggulangan Penyakit Tuberkulosis - Hendra Gunawan; Ami Kamila; Yayat Hidayat; Iyep Dede Supriyatna; Dadang Purnama (Faletehan Health Journal, 2026)
The support of the village government is still not optimal in the control of tuberculosis in Bandung Regency. The purpose of this study was to analyze the village government's support for tuberculosis disease management in Bandung Regency. The research method used was qualitative with a phenomenological approach. Participants consisted of five village officials: the village head, village secretary, head of the social welfare section, and the head of the Family Welfare Empowerment driving team. Data were collected through in-depth interviews and analyzed using thematic analysis, which included familiarizing with the data, grouping information, identifying themes, reviewing and verifying themes, defining and naming themes, and preparing the report. The results identified four main themes of village government support: integration of tuberculosis management activities in the village development plan within the village government work plan; legal support for cadres through official decree documents; financial support through the village revenue and expenditure budget; and facility support, such as the provision of village operational vehicles. Local governments should make policies that specifically regulate tuberculosis management, including support for community health cadres and the patients in village areas.